PENGARUH PEMANFAATAN KOLEKSI PERPUSTAKAAN TERHADAP PRESTASI AKADEMIK MAHASISWA - Shanti Maulani; Putri Kesuma; Wiwin Widiawati (Nusantara Journal of Information and Library Studies (N-JILS), 2021)
This study aims to determine the effect of the use of library collections on student achievement at Akper Hospital. Dustira. The method in this study uses a combination method (mixed methods) with a concurrent embedded model (unbalanced mixture). Collecting data by distributing questionnaires given to students to determine the level of utilization of collections, and observations. The data analysis technique used triangulation through interviews to dig deeper information from students and leadership elements at the Hospital Akper. Dustira especially the finance department. The results showed that the use of library collections had an effect of 72.6% to 85.7% or an average of 80%. In addition, other factors were found that support the success of students who excel academically, namely the support from the leadership element by giving awards to outstanding students in the form of award certificates and achievement support funds. Outstanding students admit that giving rewards is a separate motivation to maintain the achievements that have been achieved and even improve their academic achievements. Keywords: library collections; student achievement; Akper RS. DustiraABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh pemanfaatan koleksi perpustakaan terhadap prestasi mahasiswa di Akper RS. Dustira. Metode dalam penelitian ini menggunakan metode kombinasi (mixed methods) model concurrent embedded (campuran tidak berimbang). Pengumpulan data dengan cara penyebaran angket diberikan pada mahasiswa untuk mengetahui tingkat pemanfaatan koleksi, dan observasi. Teknik analisis data menggunakan triangulasi melalui wawancara untuk menggali informasi lebih dalam dari mahasiswa dan unsur pimpinan di Akper RS. Dustira khususnya bagian keuangan. Hasil penelitian menunjukkan bahwa pemanfaatan koleksi perpustakaan memberikan pengaruh sebesar 72,6% hingga 85,7% atau rata-rata 80%. Selain itu ditemukan faktor lain yang mendukung keberhasilan mahasiswa berprestasi secara akademik yaitu adanya dukungan dari unsur pimpinan dengan memberikan penghargaan kepada mahasiswa berprestasi berupa piagam penghargaan dan dana dukungan prestasi. Mahasiswa berprestasi mengakui bahwa pemberian reward menjadi motivasi tersendiri untuk mempertahankan prestasi yang telah diraih bahkan meningkatkan prestasinya secara akademik.